Acute Anterior Myocardial Infarction in a Patient With Dextrocardia and Situs Inversus: An Unusual Coexistence - Celik, Aziz Inan (JACC Case Rep, 2020)
Situs inversus totalis is a rare disorder. In addition, acute coronary syndromes, especially ST-segment elevation myocardial infarctions, are rarely detected in this group. We demonstrate the electrocardiographic features and discuss the interventional challenges of acute anterior myocardial infarction in a patient with dextrocardia. (Level of Difficulty: Beginner.)